ROP18-Mediated Transcriptional Reprogramming of HEK293T Cell Reveals New Roles of ROP18 in the Interplay Between Toxoplasma gondii and the Host Cell - Li, Jie-Xi; He, Jun-Jun; Elsheikha, Hany M.; Ma, Jun; Xu, Xiao-Pei; Zhu, Xing-Quan (Frontiers in Cellular and Infection Microbiology, 2020)
Toxoplasma gondii secretes a number of virulence-related effector proteins, such as the rhoptry protein 18 (ROP18). To further broaden our understanding of the molecular functions of ROP18, we examined the transcriptional response of human embryonic kidney cells (HEK293T) to ROP18 of type I T. gondii RH strain. Using RNA-sequencing, we compared the transcriptome of ROP18-expressing HEK293T cells to control HEK293T cells. Our analysis revealed that ROP18 altered the expression of 750 genes (467 upregulated genes and 283 downregulated genes) in HEK293T cells. Gene ontology (GO) and pathway enrichment analyses showed that differentially expressed genes (DEGs) were significantly enriched in extracellular matrix– and immune–related GO terms and pathways. KEGG pathway enrichment analysis revealed that DEGs were involved in several disease-related pathways, such as nervous system diseases and eye disease. ROP18 significantly increased the alternative splicing pattern “retained intron” and altered the expression of 144 transcription factors (TFs). These results provide new insight into how ROP18 may influence biological processes in the host cells via altering the expression of genes, TFs, and pathways. More in vitro and in vivo studies are required to substantiate these findings.